Inventarisasi Penyakit dan Analisis Pertanaman Jagung (Zea mays L.) dari Aplikasi Berbagai Jenis Biochar dan Pupuk Fosfor - Dini, Aci Prima; Dirmawati, Suskandini Ratih; Septiana, Liska Mutiara; Aeny, Titik Nur; Wibowo, Lestari (JURNAL AGROTROPIKA, 2024)
Maize is a leading commodity for industrial materials and food suppliers. However, corn productivity is not maximized which is caused by several factors such as physical (climate and soil type), biology (pests, pathogens, weeds), and socio-economic factors of farmers. 25% of soil types in Indonesia are Ultisol which is characterized by low pH, available P, C-organic, and productivity. There are important maize diseases that may cause yield loss such as downy mildew, blight, rust, and midrib rot. Therefore, sustainable productivity improvements are required, specifically the application of biochar and phosphor. Biochar can increase pH, C-organic, available plant nutrients, and suppress several plant diseases. This research aimed to inventory important maize diseases, the effect of biochar, phosphor, and their interaction on disease severity and incidence, growth, production, soil pH, and C-organic. This research was designed in factorial Randomized Group Design with the factors biochar with four treatment levels included no biochar (B0), rice husk biochar (B2), corn cob biochar (B2), and cassava stalk biochar (B3) at a dose of 10 tons.ha-1 and phosphor with two treatments level included no phosphor (P0) and phosphor at a dose of 222.2 kg.ha-1 (P1). The results showed that there were four important diseases after application of biochar and phosphor, which are downy mildew (Peronisclerospora sp.), blight (Bipolaris maydis), southern corn rust (Puccinia polysora), and midrib rot (Fusarium spp.). Biochar corn cobs and cassava stems suppress the incidence of blight at 6th week. Biochars increase plant height, production, and soil pH. Interactions of biochar and phosphor increase plant stem diameter. Keywords: Biochar, Disease, Maize, Phosphor